Emotional State in Relation to Physical Activity Among Older People - Agnieszka Błaszczak; Ewa Dołowy; Siemowit Muszyński (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
Old age is a stage in human life associated with alteration of physical, mental and social functioning. The aim of this study was to investigate the associations between regular physical activity (PA) and purpose of life, intensity of depressive moods, sense of coherence (SoC) and the level of anxiety in older adults. Forty six individuals physically active (A) and 49 physically inactive (NA) without mental or physical disability were included in the study. The purpose of life was assessed by Purpose of Life Scale (PIL), intensity of depressive moods by Beck Depression Inventory (BDI), SoC by Antonovsky's questionnaire and level of anxiety by State-Trait Anxiety Inventory (STAI). An AN individuals had lover BDI-feelings level compared with A group (p < 0.05). The AN group also showed a significantly lower scores in anxiety-feature domain of the STAI (p < 0.05). Our results suggest that improved self-perceived quality of life is significantly associated to PA among older adults and regular PA may be effective for improving depression and anxiety symptoms in older adults. A better understanding of the relationship between the PA and depressive moods and level of anxiety is important to develop recommendations regarding modifications in life-style.